Functional traits and adaptation of lake microbiomes on the Tibetan Plateau - Xiaoyuan Feng; Peng Xing; Ye Tao; Xiaojun Wang; Qinglong L. Wu; Yongqin Liu; Haiwei Luo (Microbiome)
Abstract Background Tibetan Plateau is credited as the “Third Pole” after the Arctic and the Antarctic, and lakes there represent a pristine habitat ideal for studying microbial processes under climate change. Results Here, we collected 169 samples from 54 lakes including those from the central Tibetan region that was underrepresented previously, grouped them to freshwater, brackish, and saline lakes, and generated a genome atlas of the Tibetan Plateau Lake Microbiome. This genomic atlas comprises 8271 metagenome-assembled genomes featured by having significant phylogenetic and functional novelty. The microbiomes of freshwater lakes are enriched with genes involved in recalcitrant carbon degradation, carbon fixation, and energy transformation, whereas those of saline lakes possess more genes that encode osmolyte transport and synthesis and enable anaerobic metabolism. These distinct metabolic features match well with the geochemical properties including dissolved organic carbon, dissolved oxygen, and salinity that distinguish between these lakes. Population genomic analysis suggests that microbial populations in saline lakes are under stronger functional constraints than those in freshwater lakes. Although microbiomes in the Tibet lakes, particularly the saline lakes, may be subject to changing selective regimes due to ongoing warming, they may also benefit from the drainage reorganization and metapopulation reconnection. Conclusions Altogether, the Tibetan Plateau Lake Microbiome atlas serves as a valuable microbial genetic resource for biodiversity conservation and climate research. Video Abstract